Controlling the resistive switching polarity in ReS2 lateral memristors through the modulation of crystal structures. (1st April 2023) - Ke, Congming; Huang, Feihong; Zhang, Zongnan; Li, Xu; Wu, Zhiming; Zhang, Chunmiao; Xu, Feiya; Wu, Yaping; Kang, Junyong
Abstract: Memristors are excellent candidates for non-volatile memory and neuromorphic computing. Controlling the resistive switching polarity in certain materials holds great promise for the design and integration of multifunctional memristors. Here, bipolar and unipolar nonvolatility were realized by modulating the crystal structures, which exhibit high switching ratios, desirable cyclability, and long retention. By investigating the defect level and conductivity difference in single-crystal and polycrystal ReS2, the competition between electric field and Joule heat effects were revealed as the essential mechanism governing the switching process and memristive polarities. These results promote the design of two-dimensional memristors with controllable polarity.